2014
DOI: 10.1186/1471-2407-14-809
|View full text |Cite
|
Sign up to set email alerts
|

MALAT1 long non-coding RNA is overexpressed in multiple myeloma and may serve as a marker to predict disease progression

Abstract: BackgroundThe pathogenesis of multiple myeloma involves complex genetic and epigenetic events. This study aimed to investigate the role and clinical relevance of the long non-coding RNA (lncRNA), metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) in multiple myeloma.MethodsBone marrow mononuclear cells were collected for analysis. The samples of multiple myeloma were taken from 45 patients at diagnosis, 61 post-treatment, and 18 who relapsed or had progression. Control samples were collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(137 citation statements)
references
References 33 publications
2
132
0
1
Order By: Relevance
“…21,22 Finally, the high level of MALAT1 can act as a marker to predict disease progression in colorectal cancer, multiple myeloma, pancreatic cancer, and non-small cell lung cancer. [23][24][25][26] However, to the best of our knowledge, the biological role and underlying mechanism of MALAT1 in liver fibrosis has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Finally, the high level of MALAT1 can act as a marker to predict disease progression in colorectal cancer, multiple myeloma, pancreatic cancer, and non-small cell lung cancer. [23][24][25][26] However, to the best of our knowledge, the biological role and underlying mechanism of MALAT1 in liver fibrosis has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 It is a poor prognostic factor in myeloma oncogenesis, and its expression increases with disease progression. [30][31][32] It is known that KDM3A promotes MALAT1 transcription by demethylating histones at its promoter region in neuroblastoma, and its upregulation could contribute to metastasis. 33 Furthermore, it has been shown that KDM3A-MALAT1-MAPK signaling contributes to cell proliferation in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These genes included those already known to act as oncogenes in myeloma, such as IGF1 and MAF (supplemental Table 5). Of the remaining candidate genes, the long noncoding RNA MALAT1 was of particular interest because it has been reported to be a poor prognostic factor in myeloma 30,31 and is involved in various antiapoptotic pathways in myeloma oncogenesis. 32 As expected, MALAT1 was upregulated during hypoxia in all 8 myeloma cell lines ( Figure 4B).…”
Section: Knockdown Of Kdm3a Induces Apoptosis In Myeloma Cells Undermentioning
confidence: 99%
“…Furthermore, eight potentially suitable works were excluded as they lacked sufficient survival data (HRs and survival curves) for analysis. Therefore, 12 eligible articles were included in this meta-analysis (Ji et al, 2003;Schmidt et al, 2011;Lai et al, 2012;Cho et al, 2014;Liu et al, 2014;Okugawa et al, 2014;Zheng et al, 2014;Hirata et al, 2015;Ma et al, 2015;Pang et al, 2015;Shen et al, 2015;Zhang et al, 2015). The main features and results of the eligible articles are summarized in Tables 1 and 2.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%